Association of serum interleukin 6 levels with clinical outcome of COVID-19 associated mucormycosis - Sivasankaran, Ramakrishnan; Mallesh, Parvathi; Chikkaiah, Prakash Banahalli; Zuhadulla, Meer; Bhagvath, Bhavana (International Journal of Advances in Medicine, 2021)
Background: Interleukin 6 (IL6) is an inflammatory cytokine and hence used as a serological marker of inflammation. COVID-19 infections induces a state of hyperinflammation which makes it conducive for opportunistic infections like mucormycosis. Methods: The prospective single-center study considered adults patients of both the gender, diagnosed with COVID-19 infection by RT-PCR technique and clinically, microbiologically or radiologically confirmed cases of mucormycosis. Necessary demographic, clinical data and serum IL6 level were collected and selected subjects were followed up until discharge or death. Subjects were classified as those who survived and succumbed to death. Chi-square test was used to analyse for categorical data between the groups. Results: The study included 61 subjects, where in there was statistically significant association between serum IL6 levels with clinical outcome of COVID-19 associated mucormycosis (CAM). Serum IL6 levels were significantly higher in patients who died. Conclusions: Higher serum IL6 levels is associated with poor clinical outcome in patients with CAM. Hence it can be used as a marker to predict prognosis of the disease.